An entrepreneurial tragi-comedy exploring the dark side of venturing - McMullan, W. Ed
An entrepreneurship educator discusses the anxiety he felt over the first 3 1/2 years developing a high-technology manufacturing business.
The author presents his final paper on the tribulations and stresses involved in founding a new high-tech manufacturing company from scratch, with colourful and valuable comments on each stage of the venture.
Keywords: Venturing